Corporate diplomacy strategy and instruments; with a discussion about "corporate diplomacy and cyclical dynamics of open innovation" - Manuel A. Egea; María Concepción Parra-Mero\~no; Gonzalo Wandosell Fernandez de Bobadilla (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper delves into the manner in which some Multinational Corporations (MNCs) manage corporate diplomacy as a catalyst of their political, social, and cultural influence in foreign markets. Once the related literature is reviewed, the qualitative Focus Group technique is applied by creating two teams of nine business internationalization experts, chosen amongst university professors; representatives of institutions and organizations, such as Chambers of Commerce or embassies; MNCs' executives and lobbyists; and high-level representatives of Spanish state diplomacy. This contribution verifies that corporate diplomacy is known and clearly distinguished from other similar functions within the company in Spain; nevertheless, it is admitted that, in the case of Spanish MNCs, the arrival of corporate diplomacy is delayed. Secondly, we present the four key instruments to exert influence and, in turn, the most necessary ones to implement corporate diplomacy strategies: networking with external stakeholders, competitive intelligence, corporate reputation, and lobbying actions. Additionally, this paper shows that some MNCs coexist with other types of diplomacy-e.g., state or political, public and commercial diplomacy, although most do not yet do so autonomously, especially the Spanish MNCs. However, MNCs foster the perception that they assume, in a certain way, the role of the nation-states. This paper's contribution is to establish that the current cross-border relational framework requires corporations to develop a true foreign policy and acquire a diplomatic know-how to strategically manage their influence in the countries where they operate so that they can obtain a "social license to operate" and generate favorable business environments. Finally, a short discussion about possible connections between corporate diplomacy and cyclical dynamics of open innovation is included, where engagement of external stakeholders and culture understanding are the main points in common identified.
Keywords: 650; corporate diplomacy; geopolitics; open innovation; soft power